Answer:
So the answer is [tex]y= (x^{4} +5x^{2}+4 )[/tex]
Step-by-step explanation:
Given;
[tex]N=4[/tex] , 'I' and '2I' are zeros and
[tex]F(-2)=40[/tex] (equation-1)
Assuming you need real coefficients so you use complex conjugate roots;
[tex]y=a\times(x-i)\times (x+i)\times (x-2i)\times (x+2i)[/tex] Where [tex]y=F(x)[/tex]
[tex]y=a\times (x^{2} -i^{2} )\times (x^{2} -4i^{2} )[/tex] (By applying [tex](a-b)(a+b)=a^{2} -b^{2}[/tex])
[tex]y=a\times(x^{2}+1 )(x^{2}+4 )[/tex] (We know [tex]i^{2} =-1[/tex] )
[tex]y=a\times (x^{4}+4x^{2} +x^{2} +4 )[/tex]
[tex]y=a\times (x^{4}+5x^{2} +4 )[/tex] (equation-2)
From equation;
[tex]x=-2[/tex] and [tex]y=40[/tex]
Plug 'x' and 'y' value in equation-2,
[tex]40=a\times ((-2)^{4}+5(-2)^{2} +4 )[/tex]
[tex]40=a\times (16+20+4)[/tex]
[tex]40=a\times 40[/tex]
[tex]a=1[/tex]
Now equation-2 become;
[tex]y=1\times (x^{4} +5x^{2}+4 )[/tex]
∴[tex]y= (x^{4} +5x^{2}+4 )[/tex]